Rugae‐like N‐doped porous carbon incorporated with Fe‐Nx and Fe3O4 dual active sites as a powerful oxygen reduction catalyst for zinc‐air batteries. (25th April 2022) - Hu, Chuan; Gu, Caixia; Guo, Man; Hu, Yan; Dong, Jiaxin; D'Souza, Lawrence; Tayirjan Taylor, Isimjan; Yang, Xiulin
Summary: The sluggish kinetics of an air cathode has limited the wide application of zinc‐air batteries. As novel powerful electrocatalysts, atomic Fe‐N‐C materials have attracted immense research interest. However, creating Fe‐N‐C and Fe3 O4 dual‐sites catalysts is still challenging. Here, we employ a facile and raw‐material‐sparse strategy to construct a zeolitic imidazolate frameworks (ZIF)‐8‐derived N‐doped carbon catalyst configured by embedded Fe‐Nx ‐C/Fe3 O4 dual sites on highly flexible carbon clothe. By soaking the precursor in the iron solution followed by pyrolysis at an optimized temperature, Fe species can translate into dual sites. Our results reveal that the optimal Fe‐NC‐950 catalyst displays an impressive quasi‐four‐electron‐transfer oxygen reduction reaction pathway exhibiting half‐wave potential ( E 1/2 ) of 0.89 V and onset potential ( E onset ) of 1.04 V. Moreover, Fe‐NC‐950 based zinc‐air cell reached a high open‐circuit voltage of 1.54 V and a power density of 165.0 mW cm −2 . Our results also showed that the trace amount of Zn species inherited from ZIF‐8 does not affect the catalyst performance. Abstract : The N‐doped carbon catalyst configured by embedded Fe‐Nx and Fe3 O4 dual sites was synthesized by immersion loading and high‐temperature conversion methods as a high‐efficient oxygen reduction reaction electrocatalyst for zinc‐air batteries. The battery delivers a high open‐circuit voltage (1.54 V) and a high power density (165.0 mW cm −2 @242 mA cm −2 ).